Gambaran Arsitektur dan Teknik Konstruksi Candi Simangambat, Kabupaten Mandailing Natal, Provinsi Sumatera Utara - Andri Restiyadi (Berkala Arkeologi Sangkhakala, 2010)
AbstractSimangambat temple is an unique temple in Northern Sumatera. The research on the temple has been done throughout 2008 until 2010. It successfully revealed the structure of brick and stone building of the temple. Its result is expected to give an idea of temple architecture and construction technique. It is considering that the architecture and construction of the temple can be associated with the character and relative periodization of the temple building .